Particulate embolization of the anterior choroidal artery in the treatment of cerebral arteriovenous malformations. - Dowd, C F; Halbach, V V; Barnwell, S L; Higashida, R T; Hieshima, G B (American Journal of Neuroradiology, 1991)
The anterior choroidal artery is commonly recruited to supply arteriovenous malformations in the temporal lobe, basal ganglia, lateral ventricle, and internal capsule. Embolization of this artery is theoretically hazardous owing to its supply to important motor territory, relative lack of collaterals, and small caliber. However, this procedure can be a beneficial adjunct to surgery or radiation in the treatment of arteriovenous malformations. We describe our experience in performing particulate embolization of the anterior choroidal artery in 15 patients (16 procedures). Significant flow reduction was achieved in 14 patients. Two symptomatic and two asymptomatic complications arose, including permanent hemiparesis in one patient.